Peningkatan Kualitas Ampas Tebu Sebagai Pakan Ternak Melalui Fermentasi dengan Penambahan Level Tepung Sagu yang Berbeda - Samadi Samadi; Sitti Wajizah; Sabda Sabda (Jurnal Agripet, 2015)
(Improvement of fermented bagasse quality as animal feed by fermentation through administration of sago flour at different levels)ABSTRACT. Feed plays an important role in livestock production system. Due to limitation of pasture and forege areas, it needs to find new feed alternative as replacement of forage as animal feed. One of feed alternatives as replacement of forage is bagasse. Bagasse has low nutritive content and digestibility. One of the efforts to improve bagasse quality is by fermentation. The purpose of this experiment was to improve nutritive values of bagasse by fermentation method by using Trichoderma harzianum as inoculum. This research was conducted at Animal Nutrition Laboratory, Animal Husbandry Department, Agricultural Faculty, Syiah Kuala University, Banda Aceh from January to April 2015. The experiment was designed by completely randomized design (CRD) with 4 treatments (addition of sago flour at defferent levels); R1 control (0% sago flour), R2 (5% sago flour), R3 (10% sago flour), R4 (15% sago flour) of fermented material. Each treatment has 4 replications, therefore there were 16 units of treatment. Parameters observed in this experiment were nutritive values of fermented bagasse including the contents of dry matter, crude protein, crude fiber and ash. The results of the experiments indicated that fermented bagasse with Trichoderma harzianum by addition of various levels of sago flour had significantly effect (P0, 05) on crude fiber and ash contents. However, there were not significantly difference (P0, 05) on dry matter and crude protein contents. In conclusion, addition of various levels of sago flour by using Trichoderma harzianum at fermented bagasse was able to improve nutritive values of fermented bagasse.